(3eZfi GdeMJGL Edi eYQaI CdaGX GdefgGLs - (3CHh YHO Gddg eMeO GdNWjH GdTQHjfis; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdHjY s
(3BNQgG (B:s
(3jfJgi HBNQ cJGH GdLYGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
Keywords: (3Gdabg GdTGaYjs